2017
DOI: 10.1002/14651858.cd011332.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Foam dressings for treating pressure ulcers

Abstract: It is uncertain whether foam dressings are more clinically effective, more acceptable to users, or more cost effective compared to alternative dressings in treating pressure ulcers. It was difficult to make accurate comparisons between foam dressings and other dressings due to the lack of data on reduction of wound size, complete wound healing, treatment costs, or insufficient time-frames. Quality of life and patient (or carer) acceptability/satisfaction associated with foam dressings were not systematically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…[ 20 , 21 ] Nonetheless, there is a lack of evidence to help us decide which dressing is clinically cost-effective. [ 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 , 21 ] Nonetheless, there is a lack of evidence to help us decide which dressing is clinically cost-effective. [ 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews produced no clear evidence that foam dressings are more effective than other dressings used for the management of diabetic foot ulcers (Dumville et al, 2013a) and pressure injuries (Walker et al, 2017). In the absence of robust evidence, clinicians are advised to take into account the wound management properties by each dressing type and to evaluate the patient, the wound, and care context when making decisions to use foam dressings (Walker et al, 2017).…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“…Two systematic reviews produced no clear evidence that foam dressings are more effective than other dressings used for the management of diabetic foot ulcers (Dumville et al, 2013a) and pressure injuries (Walker et al, 2017). In the absence of robust evidence, clinicians are advised to take into account the wound management properties by each dressing type and to evaluate the patient, the wound, and care context when making decisions to use foam dressings (Walker et al, 2017). A randomized controlled trial conducted in the USA reported that the use of a soft silicone foam dressing combined with standard preventive care provided a statistically and clinically significant benefit in reducing incidence and severity of hospital acquired pressure injuries (HAPIs) in intensive care patients when compared to patients who received standard preventive care (Kalowes et al, 2016).…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“…This technique may effectively lower the friction and chafing between PPE and the face, thereby drastically reducing skin lesions, although the integrity of the overall sealing is subject to further investigation. Recently, increasing evidence demonstrated the application of silicone foam dressing in reducing pressure ulcers (10,11). The application of padding a double-sided silicone foam dressing on the inner surface of the respirator (along the nose arch) might provide a better seal between the face and edges of the respirator (Supplementary Figure 1).…”
Section: Potential Solutionsmentioning
confidence: 99%